Vestnik Mashinostroeniya 2020
DOI: 10.36652/0042-4633-2020-5-77-78
|View full text |Cite
|
Sign up to set email alerts
|

Installation for producing of spherical metal powders for additive technologies

Abstract: A unit was developed for the production of powders of various metals with a dispersion of 0.5÷100 mm of a spherical shape and a given particle size distribution. Keywords powder, metal, spraying, sphere, dispersion. Lebedinskiy_K@mail.ru

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The studies of representatives of the genus Padus have shown that plate's bilateral asymmetry is sensitive to automobile emissions [3], therefore, the search for additional indicative features [4] for a detailed analysis of the ecological status of the environment continues [5].…”
Section: Introductionmentioning
confidence: 99%
“…The studies of representatives of the genus Padus have shown that plate's bilateral asymmetry is sensitive to automobile emissions [3], therefore, the search for additional indicative features [4] for a detailed analysis of the ecological status of the environment continues [5].…”
Section: Introductionmentioning
confidence: 99%